Evaluation of wind potential for an optimum choice of wind turbine generator on the sites of Lomé, Accra, and Cotonou located in the gulf of Guinea - Salami, Akim Adekunlé; Ajavon, Ayité Sénah Akoda; Kodjo, Mawugno Koffi; Bedja, Koffi-Sa (International Journal of Renewable Energy Development, 2016)
This work presents the characterization and assessment of wind energy potential in annual and monthly levels of the sites of Lomé, Accra and Cotonou located in the Gulf of Guinea, and the optimal characteristics of wind turbines to be installed on these sites. Studies of characterization and the wind potential of these sites from the wind speed data collected over a period of thirteen years at a height of 10 meters above the ground, show an annual average speed of 3.52 m/s for Lomé, 3.99 m/s for Cotonou and 4.16 m/s for Accra. These studies also showed that a monthly average speed exceeding 4 m/s was observed on the sites of Cotonou and Accra during the months of February, March, April, July, August and September and during the months of July, August and September on the site of Lomé. After a series of simulation conducted using the software named PotEol that we have developed in Scilab, we have retained that the wind turbines rated speeds of ~8 to 9 m/s at the sites of Lomé and Cotonou and ~ 9 to 10 m/s on the site of Accra would be the most appropriate speeds for optimal exploitation of electric energy from wind farms at a height of 50 m above the ground.Article History: Received May 26th 2016; Received in revised form August 24th 2016; Accepted August 30th 2016; Available onlineHow to Cite This Article: Salami, A.A., Ajavon, A.S.A , Kodjo, M.K. and Bédja, K. (2016) Evaluation of Wind Potential for an Optimum Choice of Wind Turbine Generator on the Sites of Lomé, Accra, and Cotonou Located in the Gulf of Guinea. Int. Journal of Renewable Energy Development, 5(3), 211-223.http://dx.doi.org/10.14710/ijred.5.3.211-223